THE EFFECT OF VITAMIN D DEFICIENCY ON EXERCISE CAPACITY, RESPIRATORY MUSCLE STRENGTH, AND PERIPHERAL MUSCLE STRENGTH IN PATIENTS WITH CONNECTIVE TISSUE DISEASES - Sari, F.; Sarac, D.; Bayram, S.; Yentur, S. Baglan; Tore, N. G.; Oskay, D.; Tufan, A. (Bmj Publishing Group, 2023)
[Abstract Not Available]
European Congress of Rheumatology (EULAR) -- MAY 31-JUN 03, 2023 -- Milan, ITALY
Keywords: Vitamin D; Systemic sclerosis; Systemic lupus erythematosus